2009
DOI: 10.1089/ars.2008.2073
|View full text |Cite
|
Sign up to set email alerts
|

H2S Protects Against Methionine–Induced Oxidative Stress in Brain Endothelial Cells

Abstract: Homocysteine (Hcy) causes cerebrovascular dysfunction by inducing oxidative stress. However, to date, there are no strategies to prevent Hcy-induced oxidative damage. Hcy is an H 2 S precursor formed from methionine (Met) metabolism. We aimed to investigate whether H 2 S ameliorated Met-induced oxidative stress in mouse brain endothelial cells (bEnd3). The bEnd3 cells were exposed to Met treatment in the presence or absence of NaHS (donor of H 2 S). Met-induced cell toxicity increased the levels of free radica… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
111
0
1

Year Published

2011
2011
2022
2022

Publication Types

Select...
8
2

Relationship

4
6

Authors

Journals

citations
Cited by 150 publications
(114 citation statements)
references
References 61 publications
2
111
0
1
Order By: Relevance
“…In tissues such as the brain, where CBS is dominant, enhanced H 2 S production might be a significant outcome of oxidative stress-induced glutathionylation. H 2 S has been shown to protect against oxidative stress in brain cells (25,52) and in HUVECs (55).…”
Section: Fig 8 Location Of Cys346mentioning
confidence: 99%
“…In tissues such as the brain, where CBS is dominant, enhanced H 2 S production might be a significant outcome of oxidative stress-induced glutathionylation. H 2 S has been shown to protect against oxidative stress in brain cells (25,52) and in HUVECs (55).…”
Section: Fig 8 Location Of Cys346mentioning
confidence: 99%
“…Inhibition of 'oxidative stress' by inactivating enzymes or the direct 'scavenging' of the oxidant species would be expected to contribute to the many potential anti-inflammatory effects of H 2 S. In vitro experiments have shown that H 2 S generated from sulfide salts (Na 2 S and NaSH) inhibits cellular damage and intracellular protein oxidation induced by HOCl [77,78], ONOO - [79] and • NO [34,80]. NaSH is also reported to scavenge and/or degrade lipid peroxides [81,82] and inhibit the expression and activity of NAD(P)H oxidase [83,84]. Increased hepatic glutathione (GSH) synthesis and decreased lipid peroxidation are also observed with Na 2 S treatment in a murine hepatic ischemia-reperfusion injury model [85].…”
Section: Antioxidant Activity Of H 2 S?mentioning
confidence: 99%
“…24 Briefly, cells were incubated with the dye for 20 minutes at 371C, washed with phosphate-buffered saline, and analyzed through laser scanning confocal microscope (  60, and  100 objective, FluoView 1000; Olympus, Center Valley, PA, USA). For flow cytometry, the cells were scrapped and subjected to Accuri's C6 Flow Cytometer (Accuri Cytometers, Ann Harbor, MI, USA).…”
Section: Measurement Of Reactive Oxygen Species Thorough Confocal Andmentioning
confidence: 99%